Time‐course changes in liver functional reserve after successful sofosbuvir/velpatasvir treatment in patients with decompensated cirrhosis. Issue 3 (17th December 2021) - Atsukawa, Masanori; Tsubota, Akihito; Kondo, Chisa; Toyoda, Hidenori; Nakamuta, Makoto; Takaguchi, Koichi; Watanabe, Tsunamasa; Hiraoka, Atsushi; Uojima, Haruki; Ishikawa, Toru; Iwasa, Motoh; Tada, Toshifumi; et al.
Abstract: Aim: Direct‐acting antivirals (DAAs) are currently available even for patients with decompensated cirrhosis. Reportedly, hepatic functional reserve improved in the short term after achievement of sustained virologic response (SVR). We aimed to clarify the outcomes after achievement of SVR in patients with decompensated cirrhosis who were treated by DAAs in real‐world clinical practice. Methods: A prospective, multicenter study of 12‐week sofosbuvir/velpatasvir was conducted in 86 patients with decompensated cirrhosis, who were evaluated for 48 weeks post‐treatment. Results: The cohort included 8 patients with Child–Pugh class A, 56 with B, and 22 with C. The proportion of Child–Pugh class A patients increased from 9.1% at baseline to 44.1% at 48 weeks post‐treatment, while that of class B and C patients decreased from 66.2% to 35.1% and from 24.7% to 14.3%, respectively. Among the patients with Child–Pugh class B and C, univariate analysis identified low total bilirubin, Child–Pugh score, Child–Pugh class B, ALBI score, and high serum albumin as factors associated with improvement to Child–Pugh class A. The optimal cut‐off value of the factors for predicting improvement to Child–Pugh class A were 1.4 mg/dl for total bilirubin, 2.9 g/dl for serum albumin, 8 points for Child–Pugh score, and −1.88 for ALBI score. Conclusion: Achievement of SVR with sofosbuvir/velpatasvir improved the liver functional reserve at 12 weeks post‐treatment and maintained the stable effects until 48 weeks post‐treatment in patients with decompensated cirrhosis. Specifically, the patients with less advanced conditions had the likelihood of improving to Child–Pugh class A at 48 weeks post‐treatment.